A conceptual framework and typology for explaining the outcomes of local forest management - Wollenberg, Eva Karoline (1998)
Few generalizations are currently possible about the effectiveness of local forest management, owing to a lack of common terms and concepts with which to compare the wide range of practices employed. This paper proposes a conceptual framework and typology based on four dimensions which affect the motivation, resources and capacities of local people to undertake it: (a) the objectives underlying local people's use of the forest; (b) the potential of the forest resource to meet these objectives; (c) the nature of local social arrangements; and (d) macro-level economic and political factors